1987
DOI: 10.1139/y87-120
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+–Ca2+ interaction in contractility of vascular smooth muscle: Mg2+ versus organic calcium channel blockers on myogenic tone and agonist-induced responsiveness of blood vessels

Abstract: Contractility of all types of invertebrate and vertebrate muscle is dependent upon the actions and interactions of two divalent cations, viz, calcium (Ca2+) and magnesium (Mg2+) ions. The data presented and reviewed herein contrast the actions of several organic Ca2+ channel blockers with the natural, physiologic (inorganic) Ca2+ antagonist, Mg2+, on microvascular and macrovascular smooth muscles. Both direct in vivo studies on microscopic arteriolar and venular smooth muscles and in vitro studies on different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(153 citation statements)
references
References 30 publications
5
146
1
1
Order By: Relevance
“…34 Magnesium, a natural calcium antagonist, acts on potential-operated channels, receptor-operated channels, and leak-operated channels in the cardiovascular system. 35 We previously reported the effects of magnesium on the production of extracellular MMPs in cultured rat VSMCs, 36 and recently, magnesium has been shown to inhibit capacitative Ca 2+ entry in VSMCs. 37 Li et al suggested the need for the 3 B-vitamins (folic acid, vitamin B6 and B12), together with normal physiological levels of magnesium, in order to prevent [Mg 2+ ]I depletion and occlusive cerebral diseases induced by hyperhomocysteinemia.…”
Section: Discussionmentioning
confidence: 97%
“…34 Magnesium, a natural calcium antagonist, acts on potential-operated channels, receptor-operated channels, and leak-operated channels in the cardiovascular system. 35 We previously reported the effects of magnesium on the production of extracellular MMPs in cultured rat VSMCs, 36 and recently, magnesium has been shown to inhibit capacitative Ca 2+ entry in VSMCs. 37 Li et al suggested the need for the 3 B-vitamins (folic acid, vitamin B6 and B12), together with normal physiological levels of magnesium, in order to prevent [Mg 2+ ]I depletion and occlusive cerebral diseases induced by hyperhomocysteinemia.…”
Section: Discussionmentioning
confidence: 97%
“…27 Among these, it has been reported that magnesium inhibits the effect of calcium from vascular smooth muscle sarcoplasmic reticulum by competition for a calcium receptor on a calcium-regulated efflux channel, 28 essentially acting as a calcium blocker. Recently, two cation channels of the transient receptor potential melastatin cation channel family have been identified as magnesium transporters and implicated as a signalling kinase involved in vascular smooth muscle cell growth, apoptosis, adhesion, contraction, cytoskeleton organization and migration, as well as important processes involved in vascular remodelling associated with hypertension and other vascular diseases.…”
Section: Magnesium and Hypertensionmentioning
confidence: 99%
“…It is well known that magnesium ions (Mg2+) influence the contractile response of isolated blood vessels to some endogenous vasoactive agents such as norepinephrine and serotonin (1). These experiments showed that low concen trations of Mg2+ in physiological salt solution enhance Ca2+-entry into smooth muscle cells, resulting in en hanced muscular contraction.…”
mentioning
confidence: 99%